MIGRATION TRANSFORMATIONS IN KYRGYZSTAN: TRENDS, CAUSES AND CONSEQUENCES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the dynamics of migration in Kyrgyzstan, paying special attention to current trends, the main causes and socio-economic consequences. It examines both internal and international migration, highlighting key factors such as economic inequality, employment opportunities, and demographic shifts. The analysis includes the role of remittances, the impact on local labor markets, and the social challenges faced by migrants and their families. The study also discusses policy measures and their effectiveness in managing migration flows in solving related problems.
Keywords: Migration dynamics, Kyrgyzstan, internal migration, international migration, economic factors, labor market, remittances, migration policy.